2014
DOI: 10.4291/wjgp.v5.i3.147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of alcohol associated pancreatitis

Abstract: Alcohol abuse is commonly associated with the development of both acute and chronic pancreatitis. Despite this close association, the fact that only a small percentage of human beings who abuse alcohol develop pancreatitis indicates that alcohol abuse alone is not sufficient to initiate clinical pancreatitis. This contention is further supported by the fact that administration of ethanol to experimental animals does not cause pancreatitis. Because of these findings, it is widely believed that ethanol sensitize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 80 publications
0
33
0
2
Order By: Relevance
“…Alcohol abuse is one of the major etiological factors for a variety of pancreatic disorders, including pancreatitis and diabetes [23, 24]. Numerous studies have demonstrated that ethanol and acetaldehyde exert deleterious effects on pancreatic exocrine and endocrine cells [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol abuse is one of the major etiological factors for a variety of pancreatic disorders, including pancreatitis and diabetes [23, 24]. Numerous studies have demonstrated that ethanol and acetaldehyde exert deleterious effects on pancreatic exocrine and endocrine cells [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Another life threatening inflammatory disease associated with insufficient autophagy is chronic pancreatitis (Clemens et al, 2014). Chronic pancreatitis greatly increases pancreatic cancer risk and so do other pancreatitis and pancreatic cancer risk factors, such as alcohol consumption and high caloric intake, all of which interfere with autophagy activity (Clemens et al, 2014).…”
Section: Corruption Of Autophagy By Cancer Risk Factorsmentioning
confidence: 99%
“…Chronic pancreatitis greatly increases pancreatic cancer risk and so do other pancreatitis and pancreatic cancer risk factors, such as alcohol consumption and high caloric intake, all of which interfere with autophagy activity (Clemens et al, 2014). Genetic manipulations that attenuate with autophagy lead to chronic pancreatitis in mice (Antonucci et al, 2015; Li et al, 2013).…”
Section: Corruption Of Autophagy By Cancer Risk Factorsmentioning
confidence: 99%
“…However, approximately 20% of AP progresses to severe acute pancreatitis (SAP), a disease with high morbidity and mortality (Whitcomb, 2006; Clemens et al , 2014). AP is the most common gastrointestinal disease requiring hospitalization in the United States (Peery et al , 2012; Clemens et al , 2014). In 2009, there were 275,000 admissions for AP, accounting for a direct annual cost of $2.6 billion (Peery et al , 2012).…”
Section: Introductionmentioning
confidence: 99%